Utilizing ROP in a Mobile Based Warehouse Management System for Small Retail Businesses - Setiawati, Winni; Beng, Jap Tji; Tony, Tony (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
ABC Store, a wholesale sock retailer, operates through both physical and online platforms. With increasing online sales, the company has experienced frequent stockouts due to inefficient manual inventory processes. This study aims to address these challenges by developing a mobile-based Warehouse Management System (WMS) integrated with a Reorder Point (ROP) calculation. The system was developed using the V-Shaped model, which involved requirement gathering through interviews and warehouse observations. The application was built using the lightweight Flutter framework and an SQLite local database, with testing including white-box, black-box, and User Acceptance Testing (UAT). Additionally, QR code scanning was implemented to improve document tracking and inventory management. The results indicate that the system functions as expected, with the ROP calculation effectively supporting restocking decisions and minimizing stockouts. This study contributes to the field by demonstrating the practical application of integrating simplified ROP calculation into a mobile-based WMS, highlighting its potential to improve warehouse operations for small businesses with limited infrastructure. The approach offers a scalable solution for managing inventory efficiently and cost-effectively, especially in small-scale retail settings.